Telomere sequence variability in genotypes from natural plant populations: unusual block-organized double-monomer terminal telomeric arrays - Alexander Belyayev; Ruslan Kalendar; Jiřina Josefiová; Ladislava Paštová; Farzaneh Habibi; Václav Mahelka; Bohumil Mandák; Karol Krak (Springer Science and Business Media LLC, 2023)
Background Telomeres are the nucleoprotein complexes that physically cap the ends of eukaryotic chromosomes. Most plants possess Arabidopsis -type telomere sequences (TSs). In addition to terminal TSs, more diverse interstitial TSs exists in plants. Although telomeres have been sufficiently studied, the actual diversity of TSs in land plants is underestimated. Results We investigate genotypes from seven natural populations with contrasting environments of four Chenopodium species to reveal the variability in TSs by analyzing Oxford Nanopore reads. Fluorescent in situ hybridization was used to localize telomeric repeats on chromosomes. We identified a number of derivative monomers that arise in part of both terminal and interstitial telomeric arrays of a single genotype. The former presents a case of block-organized double-monomer telomers, where blocks of Arabidopsis -type TTTAGGG motifs were interspersed with blocks of derivative TTTAAAA motifs. The latter is an integral part of the satellitome with transformations specific to the inactive genome fraction. Conclusions We suggested two alternative models for the possible formation of derivative monomers from telomeric heptamer motifs of Arabidopsis -type. It was assumed that derivatization of TSs is a ubiquitous process in the plant genome but occurrence and frequencies of derivatives may be genotype-specific. We also propose that the formation of non-canonical arrays of TSs, especially at chromosomal termini, may be a source for genomic variability in nature.
Keywords: Biology; Arabidopsis; Genetics; Telomere; Genome; Genotype; Arabidopsis thaliana; Computational biology; Gene; Mutant; type of access: open access